A washing-free immunoassay platform based on the passive movement of retroreflective micro particle and image processing - Kim, Ka Ram; Chun, Hyeong Jin; Jeong, Kwan Young; Kim, Jae Ho; Yoon, Hyun C. (22nd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2018, 2018)
In this study, washing-free immunoassay platform on retroreflective optical setup with precise signal distinguishable image processing was established and evaluated for cardiac troponin I. Washing-free immunoassay was enabled due to the passive movement, which is sedimentation property in direction of gravity, of retroreflective Janus particles as time went by. During the assay, sedimentation direction was controlled by simple inverting of the fluidic channel and unreacted RJP would remove by its own specific gravity. In addition, to ensure accuracy, the image processing of time-lapse images were applied to eliminate false signals caused by non-specific binding.
Keywords: Cardiac troponin; Fluidic channels; Janus particles; Micro particles; Non-specific binding; Optical bio-sensors; Passive movement; Time lapse images; Image processing; Retroreflective optical biosensor; Washing-free immunoassay